Anomalias congênitas em fetos bovinos abortados no Sul do Brasil. - Pavarini, Saulo Petinatti (2014)
Abortion, stillbirth and neonatal death are important causes of production losses to the livestock industry. Abortions caused by congenital anomalies may occur sporadically, or appear in epidemics. This retrospective study was conducted at Laboratory of Veterinary Pathology of Federal University of Rio Grande do Sul, and included 307 cases of bovine abortion submitted for diagnosis from September 2001 to March 2007. Most of them were from southern Brazil. Ten cases (3.25%) of congenital anomalies were seen. The most frequent congenital anomalies were artrogryposis, Amorphous globosus, and cleft palate (palatoschisis). Infectious causes were investigated, but only BVDV infection was detected by immunohistochemistry in one case, which was affected with porencephalia.